2019
DOI: 10.1002/edn3.30
|View full text |Cite
|
Sign up to set email alerts
|

Recreational water monitoring: Nanofluidic qRT‐PCR chip for assessing beach water safety

Abstract: Improved recreational water monitoring using rapid molecular genetic methods would decrease both public health risks and unnecessary beach closures. Hence, we developed a novel nanofluidic quantitative real‐time PCR (qPCR) in the OpenArray platform to (a) detect and quantify fecal indicator bacteria (FIBs; N = 2), (b) identify contaminant sources (microbial source tracking (MST); N = 7), and (c) detect human virulent pathogens (virulence gene markers; N = 15). Our water monitoring OpenArray plate reliably dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…qPCR assays can also be multiplexed to detect a limited number of targets in a single reaction. Furthermore, the recent development of qPCR array cards that enable simultaneous detection of dozens of gene targets in a single sample demonstrates the growing feasibility of direct detection of a comprehensive set of enteric pathogens alongside functional genes and fecal indicators [134][135][136][137][138][139][140][141][142].…”
Section: Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…qPCR assays can also be multiplexed to detect a limited number of targets in a single reaction. Furthermore, the recent development of qPCR array cards that enable simultaneous detection of dozens of gene targets in a single sample demonstrates the growing feasibility of direct detection of a comprehensive set of enteric pathogens alongside functional genes and fecal indicators [134][135][136][137][138][139][140][141][142].…”
Section: Detectionmentioning
confidence: 99%
“…The possibility of false negatives due to temporal and spatial variability, while partially addressable through strategies such as composite sampling, nevertheless suggests that general fecal indicators should continue to be assessed to complement direct pathogen detection efforts. Despite the recent introduction of procedures to simultaneously quantify multiple FIB, MST, and pathogen genes in under 4 hours [139], the expense, necessary expertise, and rapid pace of change likely preclude the routine application of direct pathogen detection for some time to come. Meanwhile, protecting public health in recreational waters remains an important (and legally mandated) goal.…”
Section: Applications and Recommendationsmentioning
confidence: 99%
“…We updated our MFQPCR chip format by adding MST markers (37 assays), increasing the number of pathogens targeted (22, 11, and 5 assays for bacterial, viral, and protozoan pathogens, respectively), and adding internal amplification and process controls (three assays) as well as FIB (two assays). Recently, Shahraki et al (Shahraki et al, 2019) reported a similar MFQPCR OpenArray chip to simultaneously quantify 15 bacterial pathogens, two FIB, and seven MST markers (a total of 24 target genes) for recreational water monitoring; however, the system developed in this study can provide more comprehensive data because it can quantify (i) both bacterial, viral, and protozoan pathogens, (ii) larger number of MST assays, (iii) internal amplification and process controls, and (iv) with more samples per run (up to 88 and 184 samples when using 96.96 and 192.24 chips, respectively, excluding standards and NTC).…”
Section: Discussionmentioning
confidence: 99%
“…We previously applied the MFQPCR technology (Fluidigm BioMark) to simultaneously quantify various pathogens and FIB in multiple samples (Ishii et al, 2014a; Ishii et al, 2013; Zhang and Ishii, 2018); however, these MFQPCR chips did not include assays for MST markers. Recently, Shahraki et al (Shahraki et al, 2019) reported an MFQPCR OpenArray chip to simultaneously quantify bacterial pathogens, FIB, and MST markers. However, their chip includes a limited number of assays (15 bacterial pathogens, two FIB, and seven MST markers), and therefore, may not provide comprehensive data enough to analyze correlations between pathogen and MST marker concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the basic workflow and data output is the same as for single-species qPCR. Although HT-qPCR systems have been successfully applied to microbial eDNA (Shahraki, Heath, & Chaganti, 2019;Waseem et al, 2019), to our knowledge this is the first published application of the method to aqueous macrobial eDNA. Below, we validate the sensitivity and specificity of a suite of assays (Table 1) on an OpenArray (Life Technologies) HT-qPCR platform and then compare the outcomes of this platform with those from single-species qPCR across over 500 environmental samples.…”
mentioning
confidence: 99%